1996
DOI: 10.1038/bjc.1996.3
|View full text |Cite
|
Sign up to set email alerts
|

Apparent bypass of negative selection in CD8+ tumours in CD2-myc transgenic mice

Abstract: Summary A role for antigen stimulation in lymphoid neoplasia has been postulated and is supported by indirect evidence that suggests that the interaction of antigen with both T cells and B cells may constitute an epigenetic event that can contribute to tumour induction or tumour progression. Using myc-bearing transgenic mice that develop mainly clonal T-cell lymphomas we have investigated the possibility that endogenous antigen-mediated clonal deletion might be overridden in tumorigenesis. CD2-myc transgenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Similarly, 9/9 of the CD2-myc cohort were also CD4 + /CD8 + . These results agree with previous, more extensive, analyses of CD2-myc tumours in which 70% of tumours belong to the CD4 + /CD8 + phenotype 25 and demonstrate that the lpr background did not alter the tumour phenotype.…”
Section: Myc Induced Lymphomagenesis Is Not Accelerated In Lpr Micesupporting
confidence: 83%
“…Similarly, 9/9 of the CD2-myc cohort were also CD4 + /CD8 + . These results agree with previous, more extensive, analyses of CD2-myc tumours in which 70% of tumours belong to the CD4 + /CD8 + phenotype 25 and demonstrate that the lpr background did not alter the tumour phenotype.…”
Section: Myc Induced Lymphomagenesis Is Not Accelerated In Lpr Micesupporting
confidence: 83%
“…Indeed, this speculative model has parallels with models of Myc-driven tumorigenesis (29,36) and provides a possible link between the development of inflammatory disease and lymphomagenesis in lck-Cre-Mnt flox/flox mice. Interestingly, c-Myc has been implicated in both negative selection and positive selection and strong transient activation of c-Myc can, like loss of Mnt, deplete DP T cells in vivo (5,40,43). Although there is no direct evidence indicating that Myc-induced apoptosis is linked to the development of inflammatory disease in transgenic mice, there is evidence that links a bypass in negative selection to Myc-induced T-cell lymphomagenesis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, c-Myc has been implicated in both negative selection and positive selection and strong transient activation of c-Myc can, like loss of Mnt, deplete DP T cells in vivo (5,40,43). Although there is no direct evidence indicating that Myc-induced apoptosis is linked to the development of inflammatory disease in transgenic mice, there is evidence that links a bypass in negative selection to Myc-induced T-cell lymphomagenesis (5). The issues of whether the inflammatory disease in lck-Cre-Mnt flox/flox mice is associated with defects in negative selection (in addition to Th1 cytokine skewing) and whether such defects are linked to lymphomagenesis can be tested with established mouse models that employ antigen-specific TCRs and ones in which apoptosis associated with negative selection is disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…One transducing virus contained the myc oncogene, while the other contained a processed and structurally intact TcR 5-chain (Fulton et al, 1987). This observation suggested that oncogenic complementation between myc and the transduced TcR Pchain may have favoured clonal outgrowth, leading us to develop a murine model, the CD2-myc mice, to further investigate the involvement of the TcR in myc-induced lymphomagenesis (Cameron et al, 1996). The CD2-myc transgenic mice develop thymic tumours exclusively.…”
mentioning
confidence: 99%
“…This limited phenotypic heterogeneity suggests that thymocytes are most susceptible to myc transformation at the *Present address: Wellcome Institute, Department of Biochemistry, University of Dundee, Dundee DD1 4HN, UK developmental stage(s) when selection events are expected. We have previously reported that a small number of these tumours comprised T-cells that expressed a potentially autoreactive TcR VP chain (Cameron et al, 1996) and that such tumours were significantly associated with the mature CD3+CD8 SP phenotype. These results suggested that negative selection or clonal anergy may be bypassed and that endogenous antigen may generate additional proliferative signals.…”
mentioning
confidence: 99%